IMPLEMENTATION OF NEP 2020 IN SCHOOL EDUCATION - Mamatha Kumari; Jayashree K. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
The National Education Policy 2020 envisions an India centered education system that contributes directly to transforming our nation sustainably into an equitable and vibrant knowledge society by providing high quality education to all. The Union Cabinet in JULY 2020 approved the new Education Policy (NEP). This aims at universalization of education from preschool to secondary level. Education improves everyone’s knowledge, skills and develops personality and attitude. To get success in life, it is very important to be educated. No one can achieve anything without education. Therefore, a new education policy has been implemented for better education in India. The teacher must be at the centre of the fundamental reforms in the education system. The new education policy must help re-establish teachers at all levels as the most respected and essential members of our society because they truly shape our next generation. The foundational principles of NEP 2020 are Access, Equity, Quality, Affordability and Accountability. The policy believes that the education system should develop good human beings with rational thinking, compression, empathy, courage, scientific temper, creative imagination and ethical values. In order to understand the features of the current education policy 2020, various provisions of this will have to be interpreted on the basis of which we will evaluate whether the national education policy 2020 in progressive or not. Many changes were made in the national educational policy such as the 5+3+3+4 system being adopted in place of the earlier 10+2 formula.